La copropriété, quinze ans après - Comtois, Roger (Assurances)

(untitled) (HEC Montréal, 1987)
We are pleased to once again present an article by Mr. Roger Comtois who has accepted our invitation to give us an assessment of the co-ownerhsip regime, fifteen years after the adoption of the Act relating thereto on the eve of a reform in this area. ln his article, our collaborator presents the difficulties encountered by the experts in this field, recommends solutions and, lastly, reviews the jurisprudence relevent to the declaration of co-ownership.